Le territoire comme lieu privilegie de transmission des savoirs et des valeurs des femmes Atikamekw - Basile, Suzy; Asselin, Hugo; Martin, Thibault (Recherches Feministes, 2017)
L’analyse thématique de 32 entrevues réalisées avec des femmes Atikamekw révèle qu’elles connaissent le mode de vie de leurs ancêtres et le rôle que les femmes y jouaient, que ce rôle était prédominant et essentiel dans l’organisation spatiale des activités traditionnelles sur le territoire, que les accouchements sont des marqueurs spatiotemporels, que la désignation du lieu d’origine a changé à la suite des bouleversements sociaux et territoriaux, que la désignation des personnes par le nom traditionnel est toujours en usage, que les femmes Atikamekw étaient responsables de l’éducation. L’obligation d’envoyer les enfants dans les pensionnats de 1955 à 1972 a provoqué une cassure dans la transmission des savoirs sur le territoire et les différentes formes de colonisation ont érodé peu à peu l’influence des femmes.
Keywords: amériques; approches et analyses; canada; care; corps; cours; féminisme autochtone; histoire et politique; intersectionnalité; justice reproductive; justice sociale; maternité; nation Atikamekw; pensionnats; pol4105; premier cycle; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; transmissions; violences; éducation

Walking With Our Sisters: une commemoration artistique pour le feminicide autochtone, en marche vers la decolonisation - Bruneau, Julie (Recherches Feministes, 2017)
In reaction to the indigenous femicide in Canada, and to the inaction of the canadian government, the victim's relatives and grassroots indigenous women groups created various memorials. The author focuses on the commemorative art installation Walking With Our Sisters, project of the Métis artist Christi Belcourt. Thus, the author led a field survey, to better understand if it was an empowering experience for the women participants. She will also question the definition of western feminism, in contrast with indigenous feminism.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; art contemporain; artistes autochtones; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; femmes* artistes; féminicide; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; militance; mémoire; mémorial; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; violences

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires